Study of immersion effectiveness in VR-based stress therapy - Mahalil I.; Rusli M.E.; Yusof A.M.; Yusoff M.Z.M.; Zainudin A.R.R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Stresses; Comparative studies; Emotional response; Immersion; Malaysians; Negative works; Virtual reality therapies; Virtual reality